Effects of chemotherapy and immunotherapy on microbial diversity in TME and engineered bacterial-mediated tumor therapy - Zheng, Heng; Chen, Xianxian; Li, Qiyang; Liu, Yuqi; Cai, Jinzhong (Frontiers in Immunology, 2023)
Abstract: The tumor microbiome, a class of microorganisms located within tumor tissues, is rich in diversity and can contribute to tumorigenesis and progression, and different types of tumors have different tumor microbiomes, which has important implications for tumor research, detection, and clinical treatment. In this review, the authors examine the diversity of the tumor microbiome, discuss the impact of chemotherapy and immunotherapy on tumor microbiome diversity, and summarize recent advances in the use of genetically engineered bacteria for the treatment of tumors. In addition, we propose key questions that need to be further addressed by the tumor microbiome.